KOMUNITAS ARTROPODA PENGHUNI TAJUK DI PERTANAMAN JAGUNG - ABDULLAH, TAMRIN; AGUS, NURARIATY; RAUF, AUNU (Agrotrop : Journal on Agriculture Science; Vol 1 No 2 (2011))
Canopy Arthropod Community Dwellers in Maize Planting. Dwellers the canopy arthropod community structure observed in maize planting in the Village Bajeng, District of North Polombangkeng, Takalar District, South Sulawesi. Observation of the canopy arthropod dwellers performed using suction machine. The results showed that the arthropod community on corn cropping consists of arthropod natural enemies, fitofag and other arthropods. Most of the arthropods that act as predators, which consists of four insect family is Formicidae, Coccinellidae, Carabidae, Gryllidae, and the two spider families is Lycosidae and Linyphiidae. Maize crop canopy arthropod dwellers generally is formicid, coccinellid, cicadellid, and pentatomid. In the maize crop canopy, formicid and aphid abundance were higher in the edge plots, whereas coccinellid, lycosid, and linyphiid higher in the center of the plot.
Keywords: maize, dwellers canopy arthropod